Evaluation of patients with Alzheimer's disease before and after dental treatment - Thaís de Souza Rolim; Gisele Maria Campos Fabri; Ricardo Nitrini; Renato Anghinah; Manoel Jacobsen Teixeira; José Tadeu T. de Siqueira; José Augusto Ferrari Cesari; Silvia Regina Dowgan Tesseroli de Siqueira (Arquivos de Neuro-Psiquiatria)
Oral infections may play a role in Alzheimer's disease (AD). Objective To describe the orofacial pain, dental characteristics and associated factors in patients with Alzheimer's Disease that underwent dental treatment. Method 29 patients with mild AD diagnosed by a neurologist were included. They fulfilled the Mini Mental State Exam and Pfeffer's questionnaire. A dentist performed a complete evaluation: clinical questionnaire; research diagnostic criteria for temporomandibular disorders; McGill pain questionnaire; oral health impact profile; decayed, missing and filled teeth index; and complete periodontal investigation. The protocol was applied before and after the dental treatment. Periodontal treatments (scaling), extractions and topic nystatin were the most frequent. Results There was a reduction in pain frequency (p=0.014), mandibular functional limitations (p=0.011) and periodontal indexes (p<0.05), and an improvement in quality of life (p=0.009) and functional impairment due to cognitive compromise (p<0.001) after the dental treatment. Orofacial complaints and intensity of pain also diminished. Conclusion The dental treatment contributed to reduce co-morbidities associated with AD and should be routinely included in the assessment of these patients.